Diversity, intensity and prevalence of parasites of cichlids in polluted and unpolluted end of Eleyele Dam in Ibadan, Oyo State - Simon-Oke, I.A (Advances in Aquaculture and Fisheries Management, 2017)
This study aimed to investigate the diversity, intensity and prevalence of parasites in Cichlids. A total of 354 specimens of cichlids was sampled in polluted and unpolluted ends of Eleyele River, Ibadan, Nigeria and examined for parasites. The total prevalence was 57.34%.Recovered parasites wereClinostomum tilapiae, Euclinostomum heterostomum,Neascus, Allocreadium ghanensis, Phagicola longa, Alloglossidium corti and the acanthocephalan;Acanthogyrus tilapiae and Acanthella.Clinostomum tilapiaehad higher prevalence and abundance (42.90%) with Allocreadium corti recording least abundance (0.49%).Tilapia zilli was the most abundant (41.53%) among the fish hosts but Oreochromis niloticus harboured the highest percentage of parasites (80.00%). The fish hosts in the polluted end of the river harboured the highest percentage of parasites(71.18%)against (43.50%) parasites recovered from the unpolluted end. There was a significant difference in the parasites harboured (P<0.05). Heavy infection with a broad number of parasites in fish hosts could reduce performance and productivity of the species, especially in fish farming